Inverse planning in Gamma Knife radiosurgery: a comparative planning study - Spaniol, Manon; Mai, Sabine; Zakrzewski, Tonja; Ehmann, Michael; Stieler, Florian (Physica medica, 2021)
Purpose - To determine the advantages of inverse planning using a prerelease version of Leksell Gamma Knife® (LGK) Lightning (Elekta AB, Sweden) compared to manual forward planning. - Methods - Thirty-eight patients with metastases (MET, n = 15), vestibular schwannomas (VS, n = 11) and meningiomas (MEN, n = 12), treated with LGK Icon™ at our institution, were analyzed retrospectively. For each case, an inverse (inv) and inverse full coverage (fc) treatment plan was generated using LGK Lightning and compared to the clinical plans. Several dosimetry and efficiency characteristics were compared for each indication. The mean, median difference and interquartile range were reported and the significance was assessed with a paired-sample Wilcoxon test (significance level < 0.05). Further, the inter operator variability was analyzed for multiple users. - Results - Inv and fc treatment plans show improved target coverage (up to 3.6%) for all analyzed paradigms. For inv plans, the selectivity is enhanced (MET: 2.9%; VS: 1.8%; MEN: 1%) and the organ at risk doses are significantly reduced (VS: up to 4.5%; MEN: up to 17.5%). For inv and fc plans, the beam on time (BOT) is shortened (MET: up to 7.9%; benign tumors: 49.5%). The inter operator variability analysis shows similar treatment plan quality with small differences in plan efficiency (difference in BOT: 1-3.3 min). - Conclusions - LGK Lightning allows to generate improved LGK treatment plans regarding plan quality with reduced BOT compared to manual forward plans. The inter operator variability showed that multiple users with different experiences can generate similar treatment plan quality using LGK Lightning.